Modified ionomer, modification method thereof and application of modified ionomer in membrane electrode
By using aliphatic multifunctional monomers to modify Nafion ionomers in the anode catalytic layer, its agglomeration is suppressed, and the problem of limited transmission of protons, electrons and gas-water in the anode catalytic layer is solved, thereby achieving higher electrolytic cell performance and catalyst utilization.
Patent Information
- Application Number
- CN202411872157.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The aggregation of Nafion ionomers in the existing anode catalytic layer limits the transmission of protons, electrons and gas-water, resulting in limited operation of the electrolytic cell under high current density and cannot meet the goal of commercial development of PEMWE.
By self-assembly with the side chain sulfonic acid group of the aliphatic multifunctional monomer and the Nafion ionomer side chain sulfonic acid group, the agglomeration of the ionomer and IrO2 is inhibited, and the modified ionomer promotes phase separation of the Nafion ionomer in the anode catalytic layer to form a more uniform catalyst distribution.
By optimizing the structure of the anode catalytic layer, the modified ionomer significantly improves the transmission capacity of protons and electrons, promotes the transmission of gas and water, and makes the electrolytic cell performance reach 2.98A·cm-2@1.9V@0.5mg·cm-2, and the catalyst utilization rate reaches 0.053gIr·kW-1.
Smart Images

Figure CN119684506A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic electrodes, and in particular relates to a modified ionomer and a modification method thereof and application in a membrane electrode. The modified ionomer can promote the phase separation of nafion ionomer in an anode catalyst layer in the membrane electrode. Background Art
[0002] Proton exchange membrane water electrolysis (PEMWE) has attracted widespread attention in recent years as an efficient hydrogen production technology. Due to the harsh environment of the anodic oxygen evolution reaction (OER), iridium (Ir) is usually used as an anode catalyst. However, the high cost and limited resources of iridium limit its large-scale application. In order to promote the commercial development of PEMWE, the U.S. Department of Energy (DOE) has set the 2025 PEMWE development goal (DOE 2025): 1.9V@3A cm-2@0.5mg·cm -2 However, at ultra-low precious metal loading, the transport of protons, electrons, and gas and water in the anode catalyst layer (anode catalyst layer) will be limited, making it impossible for the electrolyzer to operate at high current density. At present, the operating current density of the electrolyzer is usually less than 2A·cm -2 , the precious metal catalyst loading is as high as 2 mg cm -2 , there is still a big gap from the set target. Therefore, improving the electrolyzer performance by improving the mass transfer in the anode catalyst layer is crucial for the commercialization of PEMWE.
[0003] At present, there are two main methods to improve the material transport capacity in the anode catalyst layer of PEMWE. One method is to prepare oxygen evolution reaction (OER) catalysts with high conductivity and high catalytic activity, aiming to reduce the precious metal loading by improving the catalytic activity. Using cheap metal oxides as Ir-based catalyst supports is an effective approach, including Ir / MnO2, IrCoOx, Ir / NiO, Ir / CoOOH, Ir / Co3O4, etc. The electrochemical microenvironment of the catalyst is regulated by changing the interaction between the unique electronic structure of the uniformly dispersed active sites and the matrix material, thereby improving its intrinsic activity; the catalyst prepared using this method only needs 244mV overpotential to achieve 10mA·cm -2The current density has been greatly improved, but it still cannot meet the application requirements of PEM electrolyzers. Another approach is to change the macrostructure of the anode catalyst layer and improve the material transfer capacity, including constructing an ordered anode catalyst layer, a gradient pore-forming anode catalyst layer, etc. For example, Dong et al. used a nanoimprinting method to prepare an anode catalyst layer with a gradient conical array structure. This gradient conical array structure can expose more active sites, increase catalyst utilization, and improve electron and gas-water transfer capacity. Jiang et al. used a hydrothermal method to prepare an ordered array nanostructured electrode to achieve efficient gas-liquid transfer at a low precious metal loading. The electrolyzer test results show that this electrode can reduce mass transfer losses and reach 2.2A·cm at a voltage of 2.0V. -2 current density. Lv et al. used pore formers to prepare an anode catalyst layer with graded pores, which reduced the overpotential by 163 mV at the same current density compared to the ordinary anode catalyst layer. At present, a large number of studies have attempted to improve the proton, electron and gas-water transport processes by changing the structure of the anode catalyst layer. These ideas are borrowed from the relatively mature fuel cells, and the Pt / C catalyst used in fuel cells has completely different properties from the IrO2 catalyst. IrO2 is very hydrophilic and has a high surface energy, while Pt / C is hydrophobic, so IrO2 itself is more likely to form agglomerates, and the strong interaction between ionomers and IrO2 makes the agglomeration phenomenon more serious. The thick ionomer film will tightly wrap the surface of the agglomerate, limit the on-board transport pathway of protons, and cause the electron transport path to be blocked. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the main purpose of the present invention is to provide a modified ionomer, which improves the performance of a membrane electrode by promoting the phase separation of Nafion ionomer in an anode catalyst layer. The present invention also provides a modification method of the modified ionomer and the application of the modified ionomer in a membrane electrode.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A modified ionomer comprises a Nafion solution and an aliphatic multifunctional monomer.
[0007] In certain specific embodiments, the aliphatic multifunctional monomer is one of aliphatic polyol, aliphatic polyamine, and aliphatic polyacid;
[0008] Furthermore, the aliphatic multifunctional monomer is an aliphatic polyol, and the aliphatic polyol is one or more of 1,4-cyclohexanedimethanol, cyclohexanedimethanol, cyclohexanediol, and cyclohexanehexaol.
[0009] In certain specific embodiments, the mass ratio of the Nafion solution to the aliphatic multifunctional monomer is 5-15:1.
[0010] In some specific embodiments, the mass concentration of the Nafion solution is 2-10 wt %.
[0011] The present invention also provides a method for modifying the aforementioned modified ionomer, comprising the following steps:
[0012] 1) Weighing Nafion solution according to the formula requirements, and ultrasonically dispersing to obtain a reaction solution;
[0013] 2) Adding aliphatic multifunctional monomers to the reaction solution and continuing ultrasonic dispersion to carry out coordination reaction.
[0014] The present invention also aims to provide a use of the aforementioned modified ionomer in a membrane electrode.
[0015] In certain specific embodiments, an oxygen evolution catalyst slurry is coated on the anode of the proton exchange membrane, wherein the oxygen evolution catalyst slurry contains the aforementioned modified ionomer.
[0016] In some specific embodiments, the oxygen evolution catalyst slurry comprises IrO2 powder, modified ionomer solution, solvent and water, and the ratio of IrO2 powder, modified ionomer solution, solvent and water is (20-40) mg: (40-60) mg: (5-10) ml: (1-5) ml.
[0017] Furthermore, the iridium content of the IrO2 powder is 70 wt %, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm.
[0018] Furthermore, the preparation method of the oxygen evolution catalyst slurry is: according to the formula requirements, water-IrO2 powder-water-n-propanol-modified ionomer solution is added and mixed in sequence, and the mixed solution is ultrasonically treated to obtain the oxygen evolution catalyst slurry.
[0019] In some specific embodiments, the preparation method of the membrane electrode is: injecting hydrogen evolution catalyst slurry into an ultrasonic sprayer, spraying it in a serpentine route, and spraying it alternately horizontally and vertically, drying after spraying, and turning it over after drying; at the same time, injecting oxygen evolution catalyst slurry into the injection pump of the ultrasonic sprayer, spraying the oxygen evolution catalyst slurry on the turned anode alternately horizontally and vertically, and drying, so as to obtain a membrane electrode.
[0020] In certain specific embodiments, the hydrogen evolution catalyst slurry comprises Pt / C powder, ionomer solution, solvent and water.
[0021] Further, the platinum content of the Pt / C powder is 40wt%, the ionomer solution is a Nafion solution with a concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm;
[0022] In certain specific embodiments, the hydrogen evolution catalyst slurry is obtained by the following preparation method:
[0023] 10-20 mg of Pt / C powder, 40-60 mg of ionomer solution, 1-3 mL of n-propanol and 3-10 mL of deionized water are mixed, and the mixed solution is subjected to ultrasonic treatment in an ice bath for 10-30 minutes to prepare a cathode hydrogen evolution catalyst slurry.
[0024] In some specific embodiments, the setting parameters of the ultrasonic spray machine are: slurry (hydrogen evolution catalyst slurry and / or oxygen evolution catalyst slurry) liquid inflow 0.3mL / min; ultrasonic power 2.2W; nozzle movement speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90°C.
[0025] Compared with the prior art, the present invention has at least the following advantages:
[0026] 1) The modified ionomer provided by the present invention uses aliphatic multifunctional monomers to self-assemble with the ionomer side chain sulfonic acid groups to inhibit the agglomeration of the ionomer and IrO2, thereby obtaining an anode catalyst layer with more micropores and more uniform distribution of the ionomer and catalyst.
[0027] 2) The modified ionomer provided by the present invention optimizes the agglomeration phenomenon by modifying the ionomer and changing the interaction between the ionomer and IrO2. The evenly distributed ionomer and IrO2 catalyst improve the proton and electron transport capacity. The porous structure promotes gas-water transport, so that the electrolyzer performance reaches 2.98A·cm -2 @1.9V@0.5mg·cm -2 , the catalyst utilization rate reached 0.053g Ir kW -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0029] Figure 1 This is a dynamic light scattering analysis diagram of the modified ionomer in Example 2 of the present invention;
[0030] Figure 2 1H NMR spectrum analysis diagram of the modified ionomer in Example 2 of the present invention;
[0031] Figure 3 This is a Fourier transform infrared (FTIR) spectrum test diagram of the modified ionomer in Example 2 of the present invention;
[0032] Figure 4 This is a small angle scattering test diagram of the modified ionomer in Example 2 of the present invention;
[0033] Figure 5 This is a SEM morphology image of the anode catalyst layer prepared from the modified ionomer in Example 2 of the present invention;
[0034] Figure 6 This is an AFM conductivity test graph of the anode catalyst layer prepared by the modified ionomer in Example 2 of the present invention;
[0035] Figure 7 This is a graph showing the electrochemical performance test of the membrane electrode prepared from the modified ionomer in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0037] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0038] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0039] Unless otherwise stated, all percentages, parts, ratios, etc. herein are by weight. The materials, methods, and examples herein are exemplary and should not be construed as limiting unless otherwise stated. The raw materials, equipment or devices used in the production and testing processes used herein, unless otherwise stated, can be purchased through commercial channels or obtained by conventional preparation methods in the art.
[0040] In the following examples, the mass fraction of Nafion solution is 5wt%, purchased from DuPont; the mass fraction of Ir in IrO2 powder is 84%, purchased from Alfa Aesar; the mass fraction of Pt / C is 40%, purchased from DuPont; the mass fraction of 1,4-cyclohexanedimethanol is 99.0%, purchased from McLean; the mass fraction of n-propanol is 99%, purchased from McLean;
[0041] The aliphatic multifunctional monomer is one of an aliphatic polyol, an aliphatic polyamine, and an aliphatic polyacid, and the aliphatic polyol is one or more of 1,4-cyclohexanedimethanol, cyclohexanedimethanol, cyclohexanediol, and cyclohexanehexaol. In the following implementation, 1,4-cyclohexanedimethanol is taken as an example for specific description.
[0042] Example 1
[0043] This embodiment provides a membrane electrode preparation method, which specifically includes the following steps:
[0044] S1: Nafion ionomer modification
[0045] Weigh 80 mg of 5 wt% Nafion solution and perform ultrasonic treatment for 10 minutes; add 10 mg of 1,4-cyclohexanedimethanol to the reaction solution and continue ultrasonic treatment for 30 minutes to complete the coordination between 1,4-cyclohexanedimethanol and Nafion ionomer, thereby obtaining a modified Nafion ionomer solution.
[0046] S2: Coating the catalyst on the surface of the proton exchange membrane,
[0047] A proton exchange membrane (commercial Nafion 115) is placed on a vacuum heating plate of an ultrasonic spray coating machine, and the catalyst slurry is sprayed on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0048] S2.1: Cathode spraying hydrogen evolution catalyst slurry
[0049] Wherein, step S2.1 specifically comprises: taking 15 mg of Pt / C powder, 50 mg of ionomer solution, 2 mL of n-propanol and 6 mL of deionized water, mixing them, and subjecting the mixed solution to ultrasonic treatment in an ice bath for 20 minutes to obtain a cathode hydrogen evolution catalyst slurry; wherein the platinum content of the Pt / C powder is 40 wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 3 wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm;
[0050] The hydrogen evolution catalyst slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed alternately horizontally and vertically along a serpentine route, and finally a cathode catalyst loading of 0.08mgPt / cm was obtained. 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0051] S2.2: Anode spraying oxygen evolution catalyst slurry
[0052] Step S2.2 is specifically as follows: 20 mg of IrO2 powder, 40 mg of modified Nafion ionomer solution (prepared in step S1), 5 mL of n-propanol and 2 mL of deionized water (added in equal amounts twice), and the mixture is added in the order of water-IrO2 powder-water-n-propanol-modified Nafion ionomer solution, and the mixed solution is ultrasonically treated for 20 minutes to obtain an anode oxygen evolution catalyst slurry; wherein the iridium content of the IrO2 powder is 70 wt%, the modified Nafion ionomer solution, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm;
[0053] The oxygen evolution catalyst slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying. The oxygen evolution catalyst slurry was sprayed alternately horizontally and vertically on the turned anode. Finally, the anode catalyst loading was 0.35 mg. Ir / cm 2 After spraying, it was dried for 30 minutes to obtain a membrane electrode.
[0054] Example 2
[0055] This embodiment provides a membrane electrode preparation method, which specifically includes the following steps:
[0056] S1: Nafion ionomer modification
[0057] Weigh 120 mg of 5 wt% Nafion solution, and ultrasonicate for 10 minutes. Add 10 mg of 1,4-cyclohexanedimethanol to the reaction solution, and continue ultrasonicating for 30 minutes to complete the coordination between 1,4-cyclohexanedimethanol and Nafion ionomer, and obtain a modified Nafion ionomer solution.
[0058] S2: Coating the catalyst on the surface of the proton exchange membrane,
[0059] A proton exchange membrane (commercial Nafion 115) is placed on a vacuum heating plate of an ultrasonic spray coating machine, and the catalyst slurry is sprayed on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0060] S2.1: Cathode spraying hydrogen evolution catalyst slurry
[0061] Wherein, step S2.1 specifically comprises: taking 15 mg of Pt / C powder, 50 mg of ionomer solution, 2 mL of n-propanol and 6 mL of deionized water, mixing them, and subjecting the mixed solution to ultrasonic treatment in an ice bath for 20 minutes to obtain a cathode hydrogen evolution catalyst slurry; wherein the platinum content of the Pt / C powder is 40 wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 3 wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm;
[0062] The hydrogen evolution catalyst slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed alternately horizontally and vertically along a serpentine route, and finally a cathode catalyst loading of 0.1mgPt / cm was obtained. 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0063] S2.2: Anode spraying oxygen evolution catalyst slurry
[0064] Step S2.2 is specifically as follows: 30 mg of IrO2 powder, 50 mg of modified Nafion ionomer solution (prepared in step S1), 7 mL of n-propanol and 3 mL of deionized water (added in equal amounts twice), and the mixture is added in the order of water-IrO2 powder-water-n-propanol-modified Nafion ionomer solution, and the mixed solution is ultrasonically treated for 20 minutes to obtain an oxygen evolution catalyst slurry for the anode; wherein the iridium content of the IrO2 powder is 70 wt%, the modified Nafion ionomer solution, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm;
[0065] The oxygen evolution catalyst slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying. The oxygen evolution catalyst slurry was sprayed alternately horizontally and vertically on the turned anode. Finally, the anode catalyst loading of 0.4 mg was obtained. Ir / cm 2 After spraying, it was dried for 30 minutes to obtain a membrane electrode.
[0066] Example 3
[0067] This embodiment provides a membrane electrode preparation method, which specifically includes the following steps:
[0068] S1: Nafion ionomer modification
[0069] Weigh 150 mg of 5 wt% Nafion solution, and ultrasonicate for 10 minutes. Add 10 mg of 1,4-cyclohexanedimethanol to the reaction solution, and continue ultrasonicating for 30 minutes to complete the coordination between 1,4-cyclohexanedimethanol and Nafion ionomer, and obtain a modified Nafion ionomer solution.
[0070] S2: Coating the catalyst on the surface of the proton exchange membrane,
[0071] A proton exchange membrane (commercial Nafion 115) is placed on a vacuum heating plate of an ultrasonic spray coating machine, and the catalyst slurry is sprayed on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0072] S2.1: Cathode spraying hydrogen evolution catalyst slurry
[0073] Wherein, step S2.1 specifically comprises: taking 15 mg of Pt / C powder, 50 mg of ionomer solution, 2 mL of n-propanol and 6 mL of deionized water, mixing them, and subjecting the mixed solution to ultrasonic treatment in an ice bath for 20 minutes to obtain a cathode hydrogen evolution catalyst slurry; wherein the platinum content of the Pt / C powder is 40 wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 3 wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm;
[0074] The hydrogen evolution catalyst slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed alternately horizontally and vertically along a serpentine route, and finally a cathode catalyst loading of 0.12mgPt / cm was obtained. 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0075] S2.2: Anode spraying oxygen evolution catalyst slurry
[0076] Step S2.2 is specifically as follows: 40 mg of IrO2 powder, 60 mg of modified Nafion ionomer solution (prepared in step S1), 10 mL of n-propanol and 5 mL of deionized water (added in equal amounts twice), are added and mixed in the order of water-IrO2 powder-water-n-propanol-modified Nafion ionomer solution, and the mixed solution is ultrasonically treated for 20 minutes to obtain an anode oxygen evolution catalyst slurry; wherein the iridium content of the IrO2 powder is 70 wt%, the modified Nafion ionomer solution, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2 MΩcm;
[0077] The oxygen evolution catalyst slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying. The oxygen evolution catalyst slurry was sprayed alternately horizontally and vertically on the turned anode. Finally, the anode catalyst loading was 0.43 mg. Ir / cm 2 After spraying, it was dried for 30 minutes to obtain a membrane electrode.
[0078] Performance Test:
[0079] This application takes Example 2 as an example to perform performance tests on the modified ionomer in the present invention and the membrane electrode containing the modified ionomer, specifically:
[0080] 1) Structural characterization
[0081] The present application conducts structural characterization on the Nafion ionomer prepared in step S1 of Example 2, specifically:
[0082] 11) The present application performs dynamic light scattering (DLS) analysis on the Nafion ionomer prepared in step S1 of Example 2. The results are as follows: Figure 1 As shown in the figure, CHDM (1,4-cyclohexanedimethanol) and Nafion form a self-assembled structure, and its dispersion is transparent; both dispersions show a single ionomer particle distribution ( Figure 1 ); the appearance of a single peak indicates that the sample is monodisperse, has a similar aggregated particle size, and has less aggregation; the existence of a single particle peak indicates that the block copolymer has successfully self-assembled into a stable structure; the average particle size of Nafion-CHDM (248.6nm) is significantly smaller than that of Nafion (340.8nm), which indicates that Nafion-CHDM dispersion has better dispersibility and stability.
[0083] 12) When the Nafion ionomer prepared in step S1 of Example 2 is used as an anode binder, it undergoes a phase transition from an aqueous dispersion to a solid state; therefore, this test example performs 1H NMR spectroscopy analysis on the solid ionomer, and the results are as follows: Figure 2 As shown, the hydroxyl hydrogen in the Nafion-CHDM ionomer mixture has an upfield shift (3.64 ppm) compared to pure CHDM (4.39 ppm), indicating that the chemical environment of the hydroxyl hydrogen of the Nafion-CHDM ionomer is close to the sulfonate group (3.63 ppm).
[0084] In addition, this test example also carried out Fourier transform infrared (FTIR) spectroscopy test on the solid ionomer, and the results are as follows: Figure 3 As shown in the figure, the hydroxyl stretching vibration peak (3,417 cm-1) in the Nafion-CHDM HP membrane is red-shifted compared to the Nafion membrane (3,477 cm-1), indicating the formation of hydrogen bonds. This relatively weak interaction reduces the molecular vibration frequency. In PFSA ionomers, the phase separation of ionic domains and non-polar regions plays a key role in their ionic conductivity and mechanical properties.
[0085] Furthermore, this test example also conducted a small angle scattering (SAS) test on the solid ionomer, and the results are as follows: Figure 4As shown in the figure, the scattering rings associated with the expansion of ionic domains in the dry Nafion membrane are almost invisible (left). However, the two-dimensional (2D) SAXS image of the Nafion-CHDM membrane shows significant scattering rings (right), indicating that the internal structure of the Nafion-CHDM membrane is uniformly distributed in all directions, corresponding to the isotropic phase separation between the hydrophilic and hydrophobic domains.
[0086] In summary, the use of CHDM to self-assemble Nafion ionomers can effectively improve the degree of ionomer phase separation and enhance the proton transfer rate.
[0087] 2) Appearance
[0088] This test example takes Example 2 as an example, and compares the uniform distribution performance of the modified Nafion ionomer solution (referred to as Nafion-CHDM) of the present invention with that of the conventional Nafion ionomer solution (referred to as Nafion), specifically:
[0089] 21) The morphology of the anode catalyst layer prepared from the modified Nafion ionomer solution and the Nafion ionomer solution (unmodified) was tested using scanning electron microscopy (SEM). Figure 5 As shown in the figure, it can be seen that when observed at a low magnification, white large blocks corresponding to large ionomer aggregates can be seen on the surface of the anode catalyst layer using the Nafion ionomer solution, while a relatively uniform surface is observed on the surface of the anode catalyst layer using Nafion-CHDM (modified Nafion ionomer solution);
[0090] 3) Conductivity test of anode catalyst
[0091] In this test example, the anode catalyst layer prepared by the modified Nafion ionomer solution and the Nafion ionomer solution (unmodified) was tested by atomic force microscopy (AFM). From the AFM conductivity measurement, the anode catalyst layer of Nafion showed obvious low electronic conductivity areas, indicating that the ionomer was unevenly distributed and the charge transfer capacity was weak ( Figure 6 ). In contrast, the Nafion-CHDM anode catalyst layer exhibited a larger area of conductive area, indicating enhanced bonding of the ionomer to the catalyst particles. This improved conductivity is consistent with the uniform dispersion observed in the height measurement, highlighting the effectiveness of Nafion-CHDM in promoting electron transport. Consistent with the in-plane conductivity test results of the anode catalyst layer, the conductivity of the Nafion-CHDM anode catalyst layer is 1.64 times that of Nafion.
[0092] Through the AFM conductivity test of the anode catalyst in this application, it can be seen that the anode catalyst layer of Nafion-CHDM has a more favorable charge transfer environment, ensuring the uniform distribution of the ionomer.
[0093] 3) Electrochemical performance
[0094] This test example tests the electrical properties of the membrane electrode prepared from the modified ionomer in this application, specifically:
[0095] A PEMWE electrolyzer using Nafion-CHDM was constructed. In the electrolysis voltage range of 1.2-2.0V, the test results are as follows Figure 7 As shown in the figure, the electrolysis current density of the Nafion-CHDM anode catalyst layer is significantly higher than that of the Nafion anode catalyst layer. The Nafion-CHDM anode catalyst layer can achieve 2.98A·cm -2 @1.9V@0.5mg PGM cm -2 Excellent performance, close to DOE 2025 target (3A·cm -2 @1.9V@0.5mg PGM cm -2 ). Accordingly, the catalyst utilization rate is 0.053g Ir kW -1 , almost reaching the International Renewable Energy Agency (IRENA) 2026 target of 0.1g Ir kW -1 half.
[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A modified ionomer, characterized in that: It includes Nafion solution and aliphatic multifunctional monomers.
2. The modified ionomer according to claim 1, characterized in that The aliphatic multifunctional monomer is one of aliphatic polyol, aliphatic polyamine and aliphatic polyacid.
3. The modified ionomer according to claim 1, characterized in that The aliphatic multifunctional monomer is an aliphatic polyol, and the aliphatic polyol is one or more of 1,4-cyclohexanedimethanol, cyclohexanedimethanol, cyclohexanediol, and cyclohexanehexaol.
4. The modified ionomer according to claim 1, characterized in that The mass ratio of the Nafion solution to the aliphatic multifunctional monomer is 5-15:
1.
5. A method for modifying a modified ionomer according to any one of claims 1 to 4, characterized in that: The steps include: 1) Weighing Nafion solution according to the formula requirements, and ultrasonically dispersing to obtain a reaction solution; 2) Adding aliphatic multifunctional monomers to the reaction solution and continuing ultrasonic dispersion to carry out coordination reaction.
6. Use of the modified ionomer according to any one of claims 1 to 4 in a membrane electrode.
7. The use according to claim 6, characterized in that: An oxygen evolution catalyst slurry is coated on the anode of the proton exchange membrane, wherein the oxygen evolution catalyst slurry contains the modified ionomer according to any one of claims 1 to 4.
8. The use according to claim 7, characterized in that: The oxygen evolution catalyst slurry comprises IrO2 powder, modified ionomer solution, solvent and water, and the ratio of the IrO2 powder, modified ionomer solution, solvent and water is (20-40) mg: (40-60) mg: (5-10) ml: (1-5) ml.
9. The use according to claim 8, characterized in that: The preparation method of the catalyst slurry is as follows: according to the formula requirements, the modified ionomer solution-water-n-propanol-IrO2 powder is added and mixed in sequence, and the mixed solution is subjected to ultrasonic treatment to obtain the oxygen evolution catalyst slurry.
10. The use according to claim 9, characterized in that: The preparation method of the membrane electrode is as follows: injecting hydrogen evolution catalyst slurry into an ultrasonic spraying machine, spraying in a serpentine route, and spraying alternately in the horizontal and vertical directions, drying after spraying, and turning over after drying; at the same time, injecting oxygen evolution catalyst slurry into the injection pump of the ultrasonic spraying machine, spraying the oxygen evolution catalyst slurry alternately in the horizontal and vertical directions on the turned anode, and drying, so as to obtain the membrane electrode.
Citation Information
Patent Citations
Anode catalyst slurry for proton exchange membrane water electrolysis hydrogen production, membrane electrode and application
CN116219475A
PEM membrane electrode anode catalyst layer slurry, preparation method thereof and membrane electrode
CN118272832A
Membrane electrode heat treatment method for changing catalyst layer ionomer cluster and application thereof
CN119133473A
Membrane electrode for alkaline water electrolysis for hydrogen production and preparation method therefor, and electrolytic cell
WO2024193079A1